Electrodeposition of Composite Materials - Adel M. A. Mohamed; Teresa D. Golden (IntechOpen, 2016)
Nanocomposite coatings have various properties that can be utilized for corrosion protection and tribological improvements. Synthesis of the nanocomposite coatings using an electrodeposition method allows unique control of the experimental parameters. By fine tuning the experimental parameters, various compositions and properties can be obtained for the nanocomposite coatings. This book covers some of the electrochemical methods used for nanocomposite coating deposition as well as discusses in detail examples of several nanocomposite coating. The corrosion and tribological performance of the nanocomposite coatings are also covered and some nanocomposite coatings are discussed for specific technological areas, such as fuel cells and microelectronics.
English
Keywords: Composite Materials; Physical Sciences; Engineering and Technology; Materials Science; Nanotechnology